2008
DOI: 10.1007/s10103-008-0635-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of kidney stones by laser-induced breakdown spectroscopy

Abstract: We performed laser-induced breakdown spectroscopy (LIBS) for the in situ quantitative estimation of elemental constituents distributed in different parts of kidney stones obtained directly from patients by surgery. We did this by focusing the laser light directly on the center, shell, and surface of the stones to find the spatial distribution of the elements inside the stone. The elements detected in the stones were calcium, magnesium, manganese, copper, iron, zinc, strontium, sodium, potassium, carbon, hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…[15,16] Chemical analysis is deemed obsolete, whereas physical analysis techniques such as XRD and IRS are currently recommended as the preferred techniques. [7,8] The use of LIBS in stone analysis has been described recently [12,13] but data supporting its use for this purpose are limited. In the present study, 65 urinary stones were comparatively assessed and analyzed using both XRD and LIBS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[15,16] Chemical analysis is deemed obsolete, whereas physical analysis techniques such as XRD and IRS are currently recommended as the preferred techniques. [7,8] The use of LIBS in stone analysis has been described recently [12,13] but data supporting its use for this purpose are limited. In the present study, 65 urinary stones were comparatively assessed and analyzed using both XRD and LIBS.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that LIBS could be successfully used for elemental analysis of urinary stones. Singh et al [12] used LIBS to analyze five urinary stone samples and found that it can successfully identify urinary stone types. Anzano and Lasheras.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this, strontium was present during early stone formation in nanobacteria studies 25 and more strontium is found in the kidney stones of older patients than in the kidney stones of younger patients. 30 Strontium has been demonstrated to interact in other hydroxyapatite biomineralization processes. Strontium in the form of strontium ranelate interacts with hydroxyapatite.…”
Section: Discussionmentioning
confidence: 99%